Arduino Source Files for the ISCI2A18 Enrichment Project "Using the Arduino Platform to Teach Neuroscience Students Information Processing and Scientific Models in the Context of the Visual System" - Goncharenko, Nickolas (My University, 2014)
These files are programs that can be uploaded to Arduino Microcontrollers through a USB cable by the Arduino IDE. The circuits required to use these programs are fully described in the Nickolas Goncharenko's second year Enrichment Project: Using the Arduino Platform to Teach Neuroscience Students Information Processing and Scientific Models in the Context of the Visual System. For access to these documents, please email the author: Nickolas Goncharenko at gonchanh@gmail.com
Keywords: Arduino; Visual Systems; Lab